Immune profiles in primary squamous cell carcinoma of the head and neck. (September 2019) - Saloura, Vassiliki; Izumchenko, Evgeny; Zuo, Zhixiang; Bao, Riyue; Korzinkin, Michael; Ozerov, Ivan; Zhavoronkov, Alex; Sidransky, David; Bedi, Atul; Hoque, Mohammad O.; Koeppen, Hartmut; Keck, Michaela K.; et al.
Highlights: TCIP-L SCCHN enriched for β-catenin, Hedgehog pathways, NSD1 mutations, EGFR amplifications. TCIL-H SCCHN enriched for MAPK/ERK, JAK/STAT pathways, CASP8 mutations, CD274 amplifications. Combination checkpoint blockade and targeting Tregs warranted in HPV+ TCIP-H SCCHN. Combination checkpoint blockade and targeting M2 macrophages warranted in HPV- TCIP-H SCCHN. Abstract: Objectives: In this study we describe the tumor microenvironment, the signaling pathways and genetic alterations associated with the presence or absence of CD8+ T-cell infiltration in primary squamous cell carcinoma of the head and neck (SCCHN) tumors. Materials and Methods: Two SCCHN multi-analyte cohorts were utilized, the Cancer Genome Atlas (TCGA) and the Chicago Head and Neck Genomics (CHGC) cohort. A well-established chemokine signature classified SCCHN tumors into high and low CD8+ T-cell inflamed phenotypes (TCIP-H, TCIP-L respectively). Gene set enrichment and iPANDA analyses were conducted to dissect differences in signaling pathways, somatic mutations and copy number aberrations for TCIP-H versus TCIP-L tumors, stratified by HPV status. Results: TCIP-H SCCHN tumors were enriched in multiple immune checkpoints irrespective of HPV-status. HPV-positive tumors were enriched in markers of T-regulatory cells (Tregs) and HPV-negative tumors in protumorigenic M2 macrophages. TCIP-L SCCHN tumors were enriched for the β-catenin/WNT and Hedgehog signaling pathways, had frequent mutations in NSD1, amplifications in EGFR and YAP1, as well as CDKN2A deletions. TCIP-H SCCHN tumors were associated with the MAPK/ERK, JAK/STAT and mTOR/AKT signaling pathways, and were enriched in CASP8, EP300, EPHA2, HRAS mutations, CD274, PDCD1LG2, JAK2 amplifications. Conclusions: Our findings support that combinatorial immune checkpoint blockade and depletion strategies targeting Tregs in HPV-positive and M2 macrophages in HPV-negative tumors may lead to improved antitumor immune responses in patients with TCIP-H SCCHN. We highlight novel pathways and genetic events that may serve as candidate biomarkers and novel targeted therapies to enhance the efficacy of immunotherapy in SCCHN patients.